From past to present: tracing Africa’s path to universal health coverage - Langat, Evaline Chepchirchir; Ward, Paul R.; Gesesew, Hailay; Mwanri, Lillian (Frontiers in Public Health, 2025)
At the 58th World Health Assembly in 2005, the international community charted a course for universal health coverage (UHC), aiming to ensure access to health care for all in need, of sufficient quality, and without causing financial hardship. At the time, barriers to accessing health care were overwhelming, particularly in low-and middle-income countries like Africa. Currently, 50 of Africa’s 54 countries are in various phases of UHC implementation. Some are developing national UHC agendas, while others have made significant progress but still face gaps in meeting UHC targets. This mini review comprehensively examines the literature to understand the temporal and contextual patterns of Africa’s pursuit of health for all, leading up to universal health coverage (UHC). We applied narrative synthesis to identify the patterns, themes, and trends in the literature. Our findings indicate that African countries share similar contextual and chronological patterns of health reforms towards healthcare for all, which mostly emphasized the importance of revitalizing primary health care (PHC). As such, with Africa striving for UHC, continued investment in a robust infrastructure for primary healthcare is essential even as countries implement complex health insurance programs as their UHC approach. This is particularly critical given the severe impact of economic crises and debt burdens on primary healthcare infrastructure four decades ago.